THE USE OF VIDEO TO IMPROVE STUDENT VOCABULARY AT 7 GRADE SMPN 1 NANGA PINOH - Hidayatul Munawaroh; Hosmila Hosmila; Rika Safitri (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2020)
The purpose of this study is to explain and describe the use of video media to improve vocabulary of 7 grade students of SMPN 1 Nanga Pinoh in the academic year 2020/2021. This study uses a qualitative descriptive method that focuses on analyzing the use of video to improve student vocabulary. This research is conducted interactively and continuosly until it is comeplete so that there are no questions to continue. The result of this study indicate that most students become more active in participating in the learning proscess using vocabulary. This indicates that the use of video to master vocabulary is considered effective to encourage students during the learning process